Impact of using different-sized touch keyboards on free-text keystroke dynamics authentication in the Arabic language - Suliman A. Alsuhibany; Afnan S. Almuqbil (Scientific Reports, 2022)
Abstract Authentication using keystroke dynamics (KD) has become an active research area due to its usability and security aspects. Nowadays, the scale of touch keyboard use has expanded to include most modern devices. Although KD typically focuses on a single device at a particular time, authentication systems are adjustable within their environments, as these systems’ users frequently switch between multiple devices. Thus, this paper assesses users’ typing behavior on different tablet devices with varying touch keyboard sizes. In particular, we empirically assess whether the validation results from free-text KD authentication vary depending on the touch keyboard size. The results reveal interesting research directions for future feasibility studies on changing the dynamic keystroke typing-pad effect on user-security and trust-authentication analysis.